The park and recreational professional's handbook - Hurd, Amy R.; Anderson, Denise M. (Illinois : Human Kinetcs, 2011)
This comprehensive resource addresses all of the essential topics that professionals must know, including program planning and evaluation, decision making, facility management, human resources, marketing, budgeting and financial planning, and policy making. Each chapter seamlessly integrates foundation concepts, the latest, research, and real-world examples to offer complete and current coverage of the topics in an easy-to-read format. The book presents readers with a complete picture of all of the skills needed for success in the field, making it a perfect resource for new and future professionals.
Introduction and overview -- Programming -- Motor development and recreation -- Evaluation and assessment -- Planning -- Maintenance -- Facility management -- Budget and finance -- Human resources : the hiring process -- Human resources : employee management -- Marketing -- Policies and decision making -- Professional development
Includes bibliographical references and index.
Keywords: RECREATION -- STUDY AND TEACHING -- UNITED STATES